Netnographic Studies in the Implementation of Accounting Information Systems (SIA) in the Facebook Group Online Community "Learning Sharia Accounting" - Mauliyah, Nur Ika; Efrina, Liona; Jumaidi, Lalu Takdir (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2024)
The concept of Information Systems has evolved into specialized applications, including Accounting Information Systems (AIS) based on Sharia principles. Studies on Sharia Accounting Information Systems are expanding beyond corporate contexts, reaching online communities through social media platforms such as the Facebook group "Belajar Akuntansi Syariah." This study aims to explore the utilization of social media as a platform for sharing, exchanging, interpreting, and applying Sharia-based accounting information. Using a netnographic method within a constructivist paradigm, this research analyzes interactions among community members. The findings reveal that discussions in the "Belajar Akuntansi Syariah" group primarily focus on topics such as the code of ethics for Sharia accountants and auditors, participation in Sharia-themed seminars or workshops, professional development opportunities for Sharia accounting graduates, digital Islamic finance training programs, and recommendations for beginner-friendly Sharia accounting books. The group also serves as a hub for promoting seminars, sharing learning resources, and fostering professional networks. This study highlights the significant role of online communities in disseminating Islamic accounting knowledge. It recommends that government institutions and relevant stakeholders in Sharia AIS management recognize and support these digital interactions to enhance the development and accessibility of Sharia accounting education.